2015
DOI: 10.1124/mol.115.099192
|View full text |Cite
|
Sign up to set email alerts
|

Biased Agonism and Biased Allosteric Modulation at the CB1Cannabinoid Receptor

Abstract: CB 1 cannabinoid receptors (CB 1 Rs) are attractive therapeutic targets for numerous central nervous system disorders. However, clinical application of cannabinoid ligands has been hampered owing to their adverse on-target effects. Ligand-biased signaling from, and allosteric modulation of, CB 1 Rs offer pharmacological approaches that may enable the development of improved CB 1 R drugs, through modulation of only therapeutically desirable CB 1 R signaling pathways. There is growing evidence that CB 1 Rs are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(180 citation statements)
references
References 65 publications
9
166
4
1
Order By: Relevance
“…Signaling bias could be exploited for enhancement of CB 1 function in HD, at the same time limiting detrimental adverse on-target effects (Laprairie et al, 2014). Cannabinoids display signaling bias (Laprairie et al, 2014;Khajehali et al, 2015). Endocannabinoids acting at CB 1 are Ga i/o -biased, whereas THC and CP are b-arrestinbiased in STHdh Q7/Q7 cells (Laprairie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Signaling bias could be exploited for enhancement of CB 1 function in HD, at the same time limiting detrimental adverse on-target effects (Laprairie et al, 2014). Cannabinoids display signaling bias (Laprairie et al, 2014;Khajehali et al, 2015). Endocannabinoids acting at CB 1 are Ga i/o -biased, whereas THC and CP are b-arrestinbiased in STHdh Q7/Q7 cells (Laprairie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A recent in vitro study has suggested another mechanism of action of CBD could involve negative allosteric modulation (NAM) at the CB1 receptor (Laprairie et al, 2015) but we have not been able to observe NAM effects at CB1 receptors when investigating CB1 receptor agonists with other NAMs (Khajehali et al, 2015). Importantly, this mechanism has not been validated in vivo.…”
Section: Introductionmentioning
confidence: 94%
“…functionally selective agonists. Biased agonism, has been identified for many therapeutically important GPCRs such as α 1 -and β-adrenergic receptors [16,[23][24][25], μ-opioid receptors (MOR) [26,27], cannabinoid receptors [28,29], D 2L and D 1 dopamine receptors [30][31][32][33], serotonin receptors [17,34,35], chemokine receptor CCR7 [36,37], gonadotropin-releasing hormone receptors [38,39], parathyroid hormone 1 receptors (PTH1R) [40,41], angiotensin 1A (AT 1A ) receptors [42] or MC4 melanocortin receptors [43].…”
Section: Przykłady Selektywności Funkcjonalnejmentioning
confidence: 99%